2016
DOI: 10.1515/eujal-2015-0039
|View full text |Cite
|
Sign up to set email alerts
|

Material scaffolding: Supporting the comprehension of migrant cleaners at work

Abstract: This is an electronic reprint of the original article. This reprint may differ from the original in pagination and typographic detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The interview data analysed in this article have been generated in nexus analytical research being carried out at the key participants' workplaces (also reported in Strömmer, 2016aStrömmer, , 2016b 1 . The first of the three steps in conducting nexus analysis is to engage in the field and discover the social actions and actors crucial in that research problem (Scollon & Scollon, 2004, p. 153).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The interview data analysed in this article have been generated in nexus analytical research being carried out at the key participants' workplaces (also reported in Strömmer, 2016aStrömmer, , 2016b 1 . The first of the three steps in conducting nexus analysis is to engage in the field and discover the social actions and actors crucial in that research problem (Scollon & Scollon, 2004, p. 153).…”
Section: Methodsmentioning
confidence: 99%
“…Trajectories are regarded here as dynamic and ongoing, without a fixed course (Wenger, 1998; see also Räisänen, 2013). This study is part of a nexus analytical (Scollon & Scollon, 2004) study conducted in the key participants' workplaces (see Strömmer, 2016aStrömmer, , 2016b. Following a nexus-analytical research design, the study regards investment in work-related language learning as a nexus of social practices where people 's historical trajectories and experiences, discourses, and interactional elements intersect.…”
Section: Apples -Journal Of Applied Language Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Källkvist (2013) focused on how different types of tasks (translation and composition) in a foreign language class for university students facilitated interaction. Strömmer (2016aStrömmer ( , 2016bStrömmer ( , 2017b has examined immigrants' language learning in cleaning work in Finland. Strömmer (2016a: 715) focused on the interaction order in particular showing how cleaners employed by outsourced services were isolated both from the work community of the cleaning company and that of the client's.…”
Section: New Perspectives On Literacy and Language Learningmentioning
confidence: 99%
“…Members of the working community have a strong influence on a professional. [10] In other words, community fosters communication skills -one could even state that the majority of professional language learning takes place at the workplace, with the support of the colleagues. [11]…”
Section: The Working Community As a Learning Environmentmentioning
confidence: 99%